Bifenthrin insecticide promotes oxidative stress and increases inflammatory mediators in human neuroblastoma cells through NF-kappaB pathway. (June 2020) - Gargouri, Brahim; Boukholda, Khadija; Kumar, Asit; Benazzouz, Abdelhamid; Fetoui, Hamadi; Fiebich, Bernd L.; Bouchard, Michèle
Abstract: The extensive application of bifenthrin (BF) insecticide in agriculture has raised serious concerns with regard to increased risks of developing neurodegenerative diseases. Recently, our group showed that BF exposure in rodent models induced oxidative stress and inflammation markers in various regions of the brain (frontal cortex, striatum and hippocampus) and this was associated with behavioral changes. This study aimed to confirm such inflammatory and oxidative stress in an in vitro cell culture model of SK-N-SH human neuroblastoma cells. Markers of oxidative stress (ROS, NO, MDA, H2 O2 ), antioxidant enzyme activities (CAT, GPx, SOD) and inflammatory response (TNF-α, IL-6, PGE2 ) were analyzed in SK-N-SH cells after 24 h of exposure to different concentrations of BF (1–20 μM). Protein synthesis and mRNA expression of the enzymes implicated in the synthesis of PGE2 were also measured (COX-2, mPGES-1) as well as nuclear factor κappaB (NF-κBp65) and antioxidant nuclear erythroid-2 like factor-2 (Nrf-2). Cell viability was analyzed by MTT-tetrazolio (MTT) and lactate dehydrogenase (LDH) assays. Exposure of SK-N-SH cells to BF resulted in a concentration-dependent reduction in the number of viable cells (reduction of MTT and increase in LDH activity). There was also a BF concentration-dependent increase in oxidative stress markers (ROS release, NO, MDA and H2 O2 ) and decrease in the activity of antioxidant enzymes (CAT and GPx activities). There was further a concentration-dependent increase in pro-inflammatory cytokines (TNF-α and IL-6) and inflammatory mediator PGE2, increase in protein synthesis and mRNA expression of inflammatory markers (COX-2, mPGES-1 and NF-κBp65) and decrease in protein synthesis and mRNA expression of antioxidant Nrf-2. Our data shows that BF induces various oxidative stress and inflammatory markers in SK-N-SH human neuroblastoma cells as well as the activation of NF-κBp65 signaling pathway. This is in line with prior results in brain regions of rodents exposed in vivo to BF showing increased oxidative stress in response to BF exposure, occurring in pro-inflammatory conditions and likely activating programmed cell death. Graphical abstract: Effect of bifenthrin (BF) on the production of reactive oxygen species (ROS), release of oxidative stress markers – lipid; peroxidation (MDA), nitric oxide (NO), hydrogen peroxides (H2 O2 ) - and the inflammatory mediators cyclooxygenase-2 (COX-2), microsomal prostaglandin synthase-1 (mPGES-1) as well as on the activation of nuclear erythroid-2 like factor-2 (Nrf-2) and nuclear factor κappaB (NF-κBp65) in SK-N-SH human neuroblastoma cells. Unlabelled Image Highlights: BF induces various oxidative stress and inflammatory markers in SK-N-SH neuroblastoma cells. BF-induced cytotoxic conditions in SK-N-SH human neuroblastoma cells in relation to the activation of NF-κBp65 pathways. Attenuation of Nrf-2 pathway by BF probably results in activation of NF-κBp65-mediated neuroinflammation.